A generic decentralized trust management framework. (18th September 2013) - Friedman, Roy; Portnoy, Amit
Summary This paper describes TRUSTPACK, a decentralized trust management framework that provides trust management as a generic service. TRUSTPACK is unique in that it does not provide a central service. Instead, it is run by many autonomous services. This design enables TRUSTPACK to alleviate privacy concerns, as well as potentially provide better personalization and scalability when compared with current centralized solutions. A major component of TRUSTPACK is a generic decentralized graph query processing framework called GRAPHPACK, which was also developed as part of this work. GRAPHPACK consists of a decentralized graph processing language as well as an execution engine, as elaborated in this paper. The paper also presents several examples and a case study showing how TRUSTPACK can be used to handle various trust management scenarios, as well as its incorporation in an existing third party P2P file sharing application. Prototypes of TRUSTPACK and GRAPHPACK are available as open source projects at http://code.google.com/p/trustpack/ and http://code.google.com/p/graphpack/, respectively. Copyright © 2013 John Wiley & Sons, Ltd.